Anti-cancer effects of p21WAF1/CIP1 transcriptional activation induced by dsRNAs in human hepatocellular carcinoma cell lines - Wu Zhi-ming; Dai Chun; Huang Ying; Zheng Cui-fang; Dong Qiong-zhu; Wang Guan; Li Xiao-wen; Zhang Xiao-fei; Li Bin; Chen Gang (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the anti-cancer effects of p21WAF1/CIP1 transcriptional activation induced by dsRNAs in hepatocellular carcinoma (HCC) cell lines. Methods: HCC cell lines BEL7402, SMMC-7721, MHCC97L, MHCC97H, and MHCCLM3 were used. HCC cells were treated with dsP21-322 (50 nmol/L), dsControl (50 nmol/L), siP21 (50 nmol/L), or mock transfection. The expression of p21 was detected using quantitative PCR and Western blot. The effects of RNA activation on HCC cells were determined using cell viability assays, apoptosis analyses and clonogenic survival assays. Western blot was also conducted to detect the expression of Bcl-xL, survivin, cleaved caspase-3, cleaved caspase-9 and cleaved PARP. Results: At 72 to 120 h following the transfection, dsP21-322 markedly inhibited the viability of HCC cells and clone formation. At the same times, dsP21-322 caused a significant increase in HCC cell apoptosis, as demonstrated with cytometric analysis. The phenomena were correlated with decreased expression levels of the anti-apoptotic proteins Bcl-xL, survivin, and increased expression of cleaved caspase-3, cleaved caspase-9 and cleaved PARP. Conclusion: RNA-induced activation of p21 gene expression may have significant therapeutic potential for the treatment of hepatocellular carcinoma and other cancers.